High vulnerability of the heart and liver to 3‐hydroxypalmitic acid–induced disruption of mitochondrial functions in intact cell systems. Issue 9 (20th June 2018) - Cecatto, Cristiane; Wajner, Alessandro; Vargas, Carmen Regla; Wajner, Simone Magagnin; Amaral, Alexandre Umpierrez; Wajner, Moacir
Abstract: Patients affected by long‐chain 3‐hydroxyacyl‐CoA dehydrogenase (LCHAD) deficiency predominantly present severe liver and cardiac dysfunction, as well as neurological symptoms during metabolic crises, whose pathogenesis is still poorly known. In this study, we demonstrate for the first time that pathological concentrations of 3‐hydroxypalmitic acid (3HPA), the long‐chain hydroxyl fatty acid (LCHFA) that most accumulates in LCHAD deficiency, significantly decreased adenosine triphosphate‐linked and uncoupled mitochondrial respiration in intact cell systems consisting of heart fibers, cardiomyocytes, and hepatocytes, but less intense in diced forebrain. 3HPA also significantly reduced mitochondrial Ca 2+ retention capacity and membrane potential in Ca 2+ ‐loaded mitochondria more markedly in the heart and the liver, with mild or no effects in the brain, supporting a higher susceptibility of the heart and the liver to the toxic effects of this fatty acid. It is postulated that disruption of mitochondrial energy and Ca 2+ homeostasis caused by the accumulation of LCHFA may contribute toward the severe cardiac and hepatic clinical manifestations observed in the affected patients. Abstract : We observed that pathological concentrations of 3‐hydroxypalmitic acid, which accumulate the most in long‐chain 3‐hydroxyacyl‐CoA dehydrogenase (LCHAD) deficiency, significantly disrupt the mitochondrial functions of the heart and the liver, with less intense effects in the brain. It is postulated that disruption of mitochondrial energy and Ca 2+ homeostasis may contribute toward the severe cardiac and hepatic clinical manifestations observed in patients with LCHAD deficiency.